2020
DOI: 10.1002/chem.202001264
|View full text |Cite
|
Sign up to set email alerts
|

Sterubin: Enantioresolution and Configurational Stability, Enantiomeric Purity in Nature, and Neuroprotective Activity in Vitro and in Vivo

Abstract: Alzheimer′s disease (AD) is a neurological disorder with still no preventive or curative treatment. Flavonoids are phytochemicals with potential therapeutic value. Previous studies described the flavanone sterubin isolated from the Californian plant Eriodictyon californicum as a potent neuroprotectant in several in vitro assays. Herein, the resolution of synthetic racemic sterubin (1) into its two enantiomers, (R)‐1 and (S)‐1, is described, which has been performed on a chiral chromatographic phase, and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 45 publications
2
22
0
Order By: Relevance
“…Furthermore, the flavanone sterubin might provide an alternative to fisetin in conditions with an excess of iron since iron did not have an impact on the beneficial effects of sterubin in the various assays. Indeed, we recently showed that sterubin is effective at preserving memory in an acute model of AD [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the flavanone sterubin might provide an alternative to fisetin in conditions with an excess of iron since iron did not have an impact on the beneficial effects of sterubin in the various assays. Indeed, we recently showed that sterubin is effective at preserving memory in an acute model of AD [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yerba santa is a plant that has been brewed into a tea and used as a bitter flavoring additive to foods historically by Native Americans [ 126 ]. Previous studies have demonstrated that sterubin extracted from Yerba santa exhibited strong neuroprotective properties and held notable potential as a neuroprotectant [ 127 , 128 ]. Recently, scientists found that sterubin is an effective iron chelator, which could inhibit ferroptosis in a dose-dependent way through increasing GSH, decreasing ROS levels and activating Nrf2/ATF4 signaling pathway in glutamate-treated HT22 cells [ 129 ].…”
Section: Natural Bioactive Compounds As Ferroptosis Regulatorsmentioning
confidence: 99%
“…This column was the only one which was able to separate all new chiral azoles in another comparative study with several polysaccharide-based columns with various CSs [ 69 ]. The same column demonstrated good enantioselectivity in the analysis of seven process-related impurities of celecoxib as well as for enantiomers of sterubin, a potential neuroprotector extracted from Eriodictyon californicum plant [ 70 , 71 ]. An interesting comparative study was performed on a Chiralcel OJ-3 (particle size 3 µm) column using both SFC and NP-LC.…”
Section: Polysaccharide-based Stationary Phasesmentioning
confidence: 99%